A comparative study on the marginal prominence of permanent maxillary central incisors among Caucasian, Chinese and Filipino populations - Chung, Alexander M.
A study was made comparing the marginal prominence of 1/1 among Caucasian, Chinese and Filipino population. Filipinos and Chinese are comparable in terms of relative marginal prominence and frequency distribution of shovel-shape character of 1/1. Caucasians have a very low frequency of shovel-shaped incisors. Most Caucasian upper central incisors have rather flat lingual surfaces manifesting only trace or no marginal ridges.